2022
DOI: 10.3390/ijms23073741
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights of Plant Growth Promoting Bacteria Mediated Drought and Salt Stress Tolerance in Plants for Sustainable Agriculture

Abstract: Climate change has devastating effects on plant growth and yield. During ontogenesis, plants are subjected to a variety of abiotic stresses, including drought and salinity, affecting the crop loss (20–50%) and making them vulnerable in terms of survival. These stresses lead to the excessive production of reactive oxygen species (ROS) that damage nucleic acid, proteins, and lipids. Plant growth-promoting bacteria (PGPB) have remarkable capabilities in combating drought and salinity stress and improving plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 292 publications
(373 reference statements)
6
65
0
1
Order By: Relevance
“…Photosynthesis determined by fluorescence indicated that the three Bacillus strains were able to improve plant fitness, bringing (Fv/Fm) to optimal values and decreasing basal stress according to F o values (Lucena et al, 2012). The decrease of PSII efficiency (ePSR; Figure 1C) together with the significant increase of energy dissipation support the ability of the three strains to alleviate oxidative stress induced by excess UV radiation and water stress, enabling a better use of resources (Ilangumaran and Smith, 2017;Sachdev et al, 2021;Gupta et al, 2022).…”
Section: Discussionmentioning
confidence: 66%
“…Photosynthesis determined by fluorescence indicated that the three Bacillus strains were able to improve plant fitness, bringing (Fv/Fm) to optimal values and decreasing basal stress according to F o values (Lucena et al, 2012). The decrease of PSII efficiency (ePSR; Figure 1C) together with the significant increase of energy dissipation support the ability of the three strains to alleviate oxidative stress induced by excess UV radiation and water stress, enabling a better use of resources (Ilangumaran and Smith, 2017;Sachdev et al, 2021;Gupta et al, 2022).…”
Section: Discussionmentioning
confidence: 66%
“…Endophytes promote the availability of Fe 3+ ions under stress, alleviating Fe 3+ shortage for their hosts and, thus, interfere with this regulatory process (cf. [ 189 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Drought represents the alarming global abiotic stress phenomenon disturbing production and productivity in agriculture [ 1 , 2 , 3 ]. The ever-increasing population addresses the efficient use of dehydrated soils in drought-prone regions.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-increasing population addresses the efficient use of dehydrated soils in drought-prone regions. Drought stress resilience mechanisms are unavoidable even in non-arid regions owing to seasonal changes [ 3 , 4 , 5 ]. Drought stress like other abiotic stress factors causes metabolic imbalance due to the accumulation of reactive oxygen species (ROS) including hydroxyl radicals (OH●), hydrogen peroxide (H 2 O 2 ), singlet oxygen ( 1 O 2 ), and superoxide radicals (−O 2 ) [ 3 , 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation